1988
DOI: 10.1161/01.hyp.12.6.600
|View full text |Cite
|
Sign up to set email alerts
|

Changes in autonomic regulation induced by physical training in mild hypertension.

Abstract: SUMMARY The adaptive effects of physical training on cardiovascular control mechanisms were studied in 11 subjects with mild hypertension. In these subjects we assessed the gain of the heart periodsystolic arterial pressure relationship in the unfit and the fit state by using 1) an open loop approach, whereby the gain is expressed by the slope of the regression of heart period as a function of systolic arterial pressure, during a phenylephrine-induced pressure rise and 2) a closed loop approach with proper sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
480
4
18

Year Published

1997
1997
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 682 publications
(526 citation statements)
references
References 36 publications
24
480
4
18
Order By: Relevance
“…These findings of significant improvements in BRS for all conditions emphasize the importance of baroreflex modulation following aerobic training, as the BRS plays a key role as a mediator of autonomic responses and overall cardiovascular morbidity and mortality. [14][15][16][17][18] Moreover, prior research has shown improved BRS after exercise training in hypertensive participants. [47][48][49] The improvement in BRS in this investigation could be in part due to a lesser sympathetic modulation and a well-known mediator of vascular stiffness.…”
Section: Baroreflex Sensitivitymentioning
confidence: 99%
See 1 more Smart Citation
“…These findings of significant improvements in BRS for all conditions emphasize the importance of baroreflex modulation following aerobic training, as the BRS plays a key role as a mediator of autonomic responses and overall cardiovascular morbidity and mortality. [14][15][16][17][18] Moreover, prior research has shown improved BRS after exercise training in hypertensive participants. [47][48][49] The improvement in BRS in this investigation could be in part due to a lesser sympathetic modulation and a well-known mediator of vascular stiffness.…”
Section: Baroreflex Sensitivitymentioning
confidence: 99%
“…[5][6][7] Favourable modifications in autonomic modulation and BP have been documented following endurance training in animals and humans. [8][9][10][11][12] Our prior study has demonstrated an augmentation in parasympathetic or vagal modulation and enhanced baroreflex sensitivity (BRS) and arterial compliance (AC) following aerobic training. [13][14][15][16][17][18][19][20][21] Not surprisingly, few of these studies assessed these effects in African-American men, not in populations other than whites.…”
Section: Introductionmentioning
confidence: 99%
“…BRS was determined from spontaneous fluctuations in the RR interval and SBP during the 15 and 6 breaths per minute recordings using the sequence method (BRS+/+, BRS−/−) [34], the alpha coefficient (Alpha low-frequency BRS) [35] and the transfer function technique (TF-BRS) [36]. In the sequence method, BRS was estimated by identifying spontaneously occurring sequences of three or more consecutive heartbeats in which both SBP and the subsequent RR intervals changed in the same direction.…”
Section: Study Populationmentioning
confidence: 99%
“…A subsequent report by Langewitz et al, 4 showed a reduction of parasympathetic tone as a significant new factor in hypertensive subjects with the index (␣). In normotensive and hypertensive subjects undergoing a 24-h continuous recording of ECG and arterial pressure, measured with a high-fidelity technique, the overall gain of the baroreceptive mech- anisms was evaluated through an invasive study 5 with an index (␣), a measure of autonomic activity. This index underwent a clear circadian variation which was smaller during the day and decreased at rest in hypertensive patients, thus confirming that neural buffering mechanisms appear attenuated in essential hypertension.…”
Section: Heart Rate Variability and Arterial Hypertensionmentioning
confidence: 99%